2013
DOI: 10.1007/s10143-013-0495-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression of vascular endothelial growth factor receptor 2 (VEGFR-2), inducible nitric oxide synthase (iNOS), and Ki-M1P in skull base chordoma: a series of 145 tumors

Abstract: Chordomas are locally invasive tumors that have a tendency to relapse despite optimal treatment. Specific biological markers might be used to describe their behavior. There is currently no agreement regarding the best way to manage intracranial chordomas. We studied the expression of vascular endothelial growth factor receptor 2 (VEGFR-2), inducible nitric oxide synthase (iNOS), and Ki-M1P in 145 paraffin-embedded tumors. The purpose of our study was to determine: (a) the role of potent angiogenic factors VEGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…According to the literature, VEGF has been shown to be expressed in 77.8% of 28 sacral chordomas 17 , 18 . Akhavan-Sigari et al 2013 19 reported low expression of VEGFR-2 in 145 clivus chordomas, yet high expression of VEGFR-2 was correlated with a poor prognosis in their samples. In addition, a recent report has described a durable stabilization of chordomas of the skull base and the sacrum, respectively, after treatment with Erlotinib, an EGFR antagonist given in combination with the antiangiogenetic agent Bevacizumab 20 .…”
Section: Discussionmentioning
confidence: 95%
“…According to the literature, VEGF has been shown to be expressed in 77.8% of 28 sacral chordomas 17 , 18 . Akhavan-Sigari et al 2013 19 reported low expression of VEGFR-2 in 145 clivus chordomas, yet high expression of VEGFR-2 was correlated with a poor prognosis in their samples. In addition, a recent report has described a durable stabilization of chordomas of the skull base and the sacrum, respectively, after treatment with Erlotinib, an EGFR antagonist given in combination with the antiangiogenetic agent Bevacizumab 20 .…”
Section: Discussionmentioning
confidence: 95%
“…Chordomas, however, remain an elusive disease for which little has been translated into clinical applications. 4 Factors that have been associated with a potentially worse prognosis in chordoma include expression of pAKT, 10 Raf-1, 28 Survivin, 8 iNOS, 2,3 Ki-M1p, 3 VEG-FR-2, 3 and mTOR, 9 as well as overexpression of CDK4, 27 brachyury, 15 PDGFR-a, 1 EGFR, 1 c-MET, 1 SPHK1, 28 and p53. 27 Furthermore, epigenetic dysregulation with miR-1 11 or miR-1237-3p downregulation, 29 or overexpression of miR-140-3p 30 or miR-155 23 has been associated with a potentially worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, chordomas and chondrosarcomas are not sensitive to chemotherapy [105,106] and there are no drugs approved for their treatment [106][107][108]. Dysregulation of different signaling pathways has been found in the development of chordomas and chondrosarcomas [109][110][111][112][113][114][115][116][117][118][119]. Agents that interrupt these signaling pathways could become attractive targets for anticancer therapy.…”
Section: Chemotherapymentioning
confidence: 99%